Understanding substrate and inhibitor interactions with Mo-nitrogenase - Chen, T (2019)
The nitrogenase enzyme is a metalloenzyme that plays a key role in the biological nitrogen cycle. Nitrogenase fixes nitrogen by catalysing the reduction of dinitrogen in the atmosphere to ammonia. The enzyme is a protein expressed by free-living soil bacteria and symbiotic bacteria living in the roots of certain plants. The dinitrogen reduction mechanism of the enzyme remains poorly understood. This thesis describes using electrochemistry and Infrared spectroscopy to study the mechanism of molybdenum (Mo)-nitrogenase. In order to overcome the complexity of electron transfer by the native reductant Fe protein coupled to the hydrolysis of ATP, a carbon working electrode was used instead of Fe protein as a reductant to supply electrons to MoFe protein. A series of known inhibitors and different possible substrates of nitrogenase (including protons, dinitrogen, acetylene, isocyanides and carbon monoxide) was introduced into this spectroelectrochemical study. Meanwhile, genetic variants of nitrogenase were also studied to determine the role of specific amino acids in the protein by this approach.